2007
DOI: 10.1016/j.virol.2007.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Murine alveolar macrophages limit replication of vaccinia virus

Abstract: Because of concerns about zoonotic transmission of monkeypox to humans and the bioterrorism threat posed by orthopoxviruses, there is renewed interest in probing cellular and molecular mechanisms of host defense to these pathogens. In particular, it is essential to understand viral-host interactions in the respiratory tract, which is the route of infection for smallpox and a likely route of transmission for monkeypox. In this study, we analyze functions of alveolar macrophages in poxvirus infection, using a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 25 publications
(31 reference statements)
2
29
2
Order By: Relevance
“…Alveolar macrophages (AMs) are strategically situated as a first lung defense against respiratory pathogens and therefore play a central role in innate host defense and in the maintenance of immunological homeostasis (6). They are capable of sensing pathogen-associated molecular patterns and of initiating innate and adaptive immune responses against invading pathogens.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Alveolar macrophages (AMs) are strategically situated as a first lung defense against respiratory pathogens and therefore play a central role in innate host defense and in the maintenance of immunological homeostasis (6). They are capable of sensing pathogen-associated molecular patterns and of initiating innate and adaptive immune responses against invading pathogens.…”
Section: Clinical Relevancementioning
confidence: 99%
“…BAL was performed as described previously (20). The first milliliter of lavage fluid was used for analyses of total protein and cytokines.…”
Section: Bronchoalveolar Lavage (Bal)mentioning
confidence: 99%
“…After inhalation, VACV-WR infects multiple cell types in the lung, including alveolar macrophages (10), dendritic cells (DCs) (11), and bronchiolar and alveolar epithelial cells (12). Over the next few days, the virus replicates exponentially in the lung, resulting in perivascular and peribronchial inflammation, hypertrophy and hyperplasia of epithelial cells, and diffuse alveolar damage (9).…”
mentioning
confidence: 99%
“…In general, it is believed that recovery from a respiratory VACV infection requires a tightly coordinated response by both the innate and adaptive immune systems. In this regard, a limited number of studies have shown that pattern recognition receptors (13)(14)(15)(16), alveolar macrophages (10), and dendritic cells direct the early response to VACV (11,17,18). As the adaptive immune response develops, virus-specific CD8 T cells play a vital role in restricting lung pathology and virus dissemination to visceral tissues and are necessary for complete clearance of virus and protection against death (19).…”
mentioning
confidence: 99%